2011
DOI: 10.1016/j.jvs.2010.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of nonaneurysmal infectious aortitis

Abstract: We report a 79-year-old patient who presented with a fever and abdominal pain. The patient was initially thought to have a retroperitoneal fibrosis or inflammatory abdominal aortitis in a normal-sized caliber aorta. Broad-range polymerase chain reaction (PCR) and DNA sequencing revealed the presence of Enterobacter. We finally diagnosed nonaneurysmal infectious aortitis, and we performed a successful surgical resection. Establishing a diagnosis of aortic infection before formation of an aneurysm is difficult. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…Nonaneurysmal infectious aortitis is more difficult to diagnose on imaging than MA, given the lack of aortic dilation, but even so may be complicated by rupture (43,44). A more recent case report described achieving an elusive diagnosis of infectious nonaneurysmal infectious aortitis by using broad-range polymerase chain reaction and DNA sequencing, which allowed for identification of the microbial species despite negative blood cultures (45).…”
Section: Nonaneurysmal Infectious Aortitismentioning
confidence: 99%
“…Nonaneurysmal infectious aortitis is more difficult to diagnose on imaging than MA, given the lack of aortic dilation, but even so may be complicated by rupture (43,44). A more recent case report described achieving an elusive diagnosis of infectious nonaneurysmal infectious aortitis by using broad-range polymerase chain reaction and DNA sequencing, which allowed for identification of the microbial species despite negative blood cultures (45).…”
Section: Nonaneurysmal Infectious Aortitismentioning
confidence: 99%
“…[6] For non-aneurysmal infectious aortitis, the incidence of non-specific symptoms is higher. [1] In the presence of penetrating injury or trauma in aortic walls, bacterial inoculation is made. Also, bacterial inoculation may occur on an atherosclerotic plaque or a pre-existing aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the diagnosis of nonaneurysmal infectious aortitis is challenging and frequently delayed. [1] Delayed treatment of non-aneurysmal infectious aortitis may result in aneurysmal changes, carrying the risk of pseudoaneurysm formation and aortic rupture. [2] In this article, we present a case of non-aneurysmal infectious aortitis who was treated with surgery and pharmacological therapy in the light of literature review.…”
mentioning
confidence: 99%
“…69) Ishizaka, et al suggested that IgG4 is also associated with the pathogenesis of infectious aneurysm and aortitis, 70) based on a case of infectious aortitis with IgG4-positive plasmacyte infiltration. 71) Etiologically, inflammatory thoracic aortic aneurysm is prevalent in old females while IAAA and retroperitoneal fibrosis are prevalent in old males, although they have similar histological features. 72) As for symptoms, abdominal or back pain was more commonly observed in patients with non-IgG4-related IAAA than IgG4-related AAA, and low grade fever was equally associated with both inflammatory AAAs.…”
Section: Igg4-related Cardiovascular Diseasementioning
confidence: 99%